Participação no judiciário: (in)efetividade das ações populares e das ações civis públicas ajuizadas por associações na seara ambiental - Ribeiro, Elen Pessoa de Queiroz (2024)
Citizen Lawsuits and Public Civil Actions, validate participatory democracy and, therefore, allows the achievement of environmental justice. Control made by the population should not only guarantee the protection of fundamental rights brought by the 1988 Federal Constitution, but, also, allow the will of the community to be respected. It reflects the Social State, whose freedoms granted to citizens allow the formation of critical thinking that transcends the individual. In this sense, the present research aimed to answer the following question: are Citizen Lawsuits and Public Civil Actions effective legal instruments that allow individuals, in the exercise of citizenship, to successfully protect the environment? To answer this question, data regarding Citizen Lawsuits and Public Civil Actions, in the state of São Paulo, in the period from 2015 to 2022, was collected in the National Register of Collective Actions of the National Council of Justice. The information found was analyzed according to the concepts of efficiency, effectiveness, according to the principle 10 of the Rio de Janeiro Declaration about Environment and Development and Sustainable Development Goal number 16 (SDG 16), which brings popular participation, access to justice and access information as essential elements to occur environmental protection by society. This research aimed to understand how these constitutional instruments were used: who were the protagonists in their use and how their treatment is carried out, once they have entered judiciary system. The data found showed that, in addition to the low number of Public Civil Actions, which were filed by associations, Popular Action also proved to be an underused instrument. The absence of popular participation is not the only factor that would explain these results: the conduction of the legal process itself also proved to be a limiting factor that discourages the use of these instruments.